Frequency ambiguity free tiered differential‐polyphase codes for GNSS signal design. Issue 9 (1st April 2017) - Han, S.K.; Kim, J.‐B.; Kim, J.‐K.; Han, A.; Kim, K.‐J.; Song, K.‐W.; Lee, S.‐J.; Ahn, J.M.
Abstract : To resolve frequency ambiguity of tiered polyphase code (TPC), a differential encoding method to the secondary code of the TPC is proposed. By performing differential decoding, the frequency ambiguity is removed and the code sequence boundary is correctly found. In addition, the correlation results at the receiver can be used as a frequency offset estimator. Analysis on the receiver operations and the simulation results show that the proposed tiered differential‐PC makes the code sequence boundary detection correctly under the frequency offset of up to several hundred hertz. The root mean squared error of the frequency offset estimation is reduced to <10 Hz under operating signal‐to‐noise power ratio which is about −35 dB.